Associations between a weighted health behaviour score, socioeconomic status, and all-cause mortality in UK Biobank cohort: a prospective analysis. (November 2022) - Foster, Hamish M E; Gill, Jason M R; Jani, Bhautesh D; Celis-Morales, Carlos; Lee, Duncan; Mair, Frances S; O'Donnell, Catherine A
Abstract: Background: Unhealthy behaviours are associated with disproportionate mortality among socioeconomically deprived populations. Previous studies exploring that disproportionate harm do not examine weighted scores, or examine few behaviours. We aimed to create an extended weighted health behaviour score and examine the effect of socioeconomic status on the association between score and all-cause mortality. Methods: Data was sourced from the UK Biobank population cohort, recruited in 2006–10. The main exposures included in the analysis were 11 health behaviours (baseline self-report): smoking status, alcohol consumption, physical activity, time spent watching television, sleep duration, added salt in diet, social isolation, intake of red meat, intake of processed meat, intake of oily fish, and intake of fruit and vegetables. Behaviours were classified as healthy or unhealthy according to national guidelines or latest evidence. Socioeconomic deprivation was measured with the Townsend deprivation index. Cox proportional hazard models of health behaviour data were prospectively linked to death registries to examine associations between health behaviours and all-cause mortality. Models were adjusted for demographics and health at baseline. Mortality associated with each behaviour alone was used to determine score weighting. For sensitivity analysis, we explored associations between weighted lifestyle score and all-cause mortality stratified by sex and ethnicity. Findings: The analysis included 229 107 participants with complete data. Median age was 53 years (IQR 47–60) for 119 634 (52·2%) women and 54 years (47–60) for 109 473 (47·8%) men. Over a median follow-up of 11·9 years (IQR 11.1–12.6), 9379 (4·1%) participants died. Compared with having no unhealthy behaviours, each behaviour was positively associated with all-cause mortality. Smoking (hazard ratio [HR] 2·47 [95% CI 2·25–2·70]) and social isolation (1·69 [1·54–1·86]) were associated with notably higher mortality. A weighted score was created by ascribing one point to each 40% increment in risk (four points for smoking, two points for social isolation, and one points for each of all other behaviours). A dose-response increment for all-cause mortality HR was noted with each additional point of weighted score. Associations were stronger in more deprived tertiles. With least deprived and lowest score as reference, HRs for highest scores were 2·22 (95% CI 1·72–2·86) in the least deprived and 4·10 (3·62–4·65) in the most deprived. An additive interaction between sex and lifestyle score for all-cause mortality was suggested by the data; men had slightly higher HRs at each level of the lifestyle score. However, a statistical test for interaction on a multiplicative scale was not significant. No evidence was found of interaction (either additive or multiplicative) between ethnicity and lifestyle score. Interpretation: An extended weighted health behaviour score has strong associations with mortality, and associations are stronger in more deprived participants. Weighted health behaviour scores that account for socioeconomic deprivation could convey personalised risk and inform healthy living policy. Further work with adequate numbers of participants from minority ethnic groups is required to make more accurate estimates of mortality associated with a weighted health behaviour score in these populations. Funding: HMEF is supported by a Medical Research Council Clinical Research Training Fellowship (grant number MR/T001585/1), which covered the costs of accessing the data herein.